Alcohol and Stress Activation of Microglia and Neurons: Brain Regional Effects. (8th November 2017) - Walter, Thomas Jordan; Vetreno, Ryan P.; Crews, Fulton T.
Abstract : Background: Cycles of alcohol and stress are hypothesized to contribute to alcohol use disorders. How this occurs is poorly understood, although both alcohol and stress activate the neuroimmune system—the immune molecules and cells that interact with the nervous system. The effects of alcohol and stress on the neuroimmune system are mediated in part by peripheral signaling molecules. Alcohol and stress both enhance immunomodulatory molecules such as corticosterone and endotoxin to impact neuroimmune cells, such as microglia, and may subsequently impact neurons. In this study, we therefore examined the effects of acute and chronic ethanol (EtOH) on the corticosterone, endotoxin, and microglial and neuronal response to acute stress. Methods: Male Wistar rats were treated intragastrically with acute EtOH and acutely stressed with restraint/water immersion. Another group of rats was treated intragastrically with chronic intermittent EtOH and acutely stressed following prolonged abstinence. Plasma corticosterone and endotoxin were measured, and immunohistochemical stains for the microglial marker CD11b and neuronal activation marker c‐Fos were performed. Results: Acute EtOH and acute stress interacted to increase plasma endotoxin and microglial CD11b, but not plasma corticosterone or neuronal c‐Fos. Chronic EtOH caused a lasting sensitization of stress‐induced plasma endotoxin, but not plasma corticosterone. Chronic EtOH also caused a lasting sensitization of stress‐induced microglial CD11b, but not neuronal c‐Fos. Conclusions: These results find acute EtOH combined with acute stress enhanced plasma endotoxin, as well as microglial CD11b in many brain regions. Chronic EtOH followed by acute stress also increased plasma endotoxin and microglial CD11b, suggesting a lasting sensitization to acute stress. Overall, these data suggest alcohol and stress interact to increase plasma endotoxin, resulting in enhanced microglial activation that could contribute to disease progression. Abstract : Cycles of alcohol and stress are thought to contribute to alcohol use disorders, but the mechanism is poorly understood. In these studies, we find that combined acute alcohol and stress enhance plasma endotoxin levels and increase brain microglial activation. Furthermore, chronic alcohol persistently sensitizes the plasma endotoxin and brain microglial response to acute stress. These results suggest cycles of alcohol and stress enhance gut leakiness, leading to increased pro‐inflammatory signaling that impacts the brain to contribute to pathology.